If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9x = 5 Combine like terms: 4x + -9x = -5x -5x = 5 Solving -5x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = -1 Simplifying x = -1
| 7.68=r*6 | | d=3*3.84 | | 2g=162 | | 6.4=r*4 | | 15x^2+25x=0 | | 8/5(10) | | 3x^2-32x+12=0 | | (1.0083)x=3 | | d=6.4*4 | | x+57+x=607 | | x+57+x=713 | | x+2x+15=72 | | 512*3=1 | | 2x+x=264 | | -29+x=4 | | 2x+16=73 | | x-57+x=593 | | x+10+x=108 | | 2x+x=249 | | 6x-13=4x+11 | | 9=7x | | x=1.25+0.75y | | 15(t-6)+6t=7(3t+5)-11 | | -2(4s-6)-12=-2(6s+5)-2 | | -3(3s-4)-12=-2(8s+10)-2 | | (4x-5)(2x-3)= | | 5x+5=(x-23) | | -18t^4+9t^3+2t= | | .6w-.3w+.2w=3 | | 7y-9y=16 | | 15x-23x=1/3 | | (10b-3)-3(3b+1)=-6 |